(untitled) (Journal of Global Accounting, 2023)
This study investigates the nexus of strategic management accounting and competitive advantage in manufacturing firms. The study adopts the survey research design. The sample for the study comprised forty accountants and forty administrative staffs from ten randomly selected manufacturing companies in Nnewi and Awka, Anambra State. The study relied on primary data; obtained from a structured questionnaire. The data were analysed using descriptive and inferential statistics. The formulated hypotheses where tested using one-sample t test. The results showed that strategic management accounting techniques significantly affects cost reduction and product differentiation decisions of manufacturing firms. This supports the fact that manufacturing firms in Anambra State can enhance their ability to achieve competitive advantage via adoption of SMA techniques. Based on this, the study recommends the use of strategic management accounting techniques, such as activity based costing for cost reduction decision making and attribute costing for product differentiation decisions making in manufacturing firms.